2012
DOI: 10.1007/8904_2012_176
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Changes and Micronutrient Supply in Patients with Phenylketonuria Under Therapy with Tetrahydrobiopterin (BH4)

Abstract: Background: Since 2008 patients with BH 4 -sensitive phenylketonuria can be treated with sapropterin dihydrochloride (Kuvan®) in addition to the classic phenylalanine (Phe) restricted diet. The aim of this study was to evaluate the nutritional changes and micronutrient supply in patients with phenylketonuria (PKU) under therapy with tetrahydrobiopterin (BH 4 ).Subjects and Methods: 19 children with PKU (4-18 years) and potential BH 4 -sensitivity were included, 14 completed the study protocol. Dried blood Phe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 31 publications
4
28
0
Order By: Relevance
“…15 However, this seems not to be true for patients with a high Phe tolerance: relaxing the diet because of increased Phe tolerance by addition of BH 4 led to decreased consumption of fruits and vegetables and consequently vitamin C supply. 10 Of concern, the intake of calcium and vitamin D is far below the recommendations, confirming earlier studies. 16 In a subgroup of 12 patients for whom plasma 25-OH-vitamin D was available, 9 showed concentrations at or below the lower limit of normal (mean ¼ 19 ng/ml; range ¼ 7.9-29.7), underlining the insufficient vitamin D supply.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…15 However, this seems not to be true for patients with a high Phe tolerance: relaxing the diet because of increased Phe tolerance by addition of BH 4 led to decreased consumption of fruits and vegetables and consequently vitamin C supply. 10 Of concern, the intake of calcium and vitamin D is far below the recommendations, confirming earlier studies. 16 In a subgroup of 12 patients for whom plasma 25-OH-vitamin D was available, 9 showed concentrations at or below the lower limit of normal (mean ¼ 19 ng/ml; range ¼ 7.9-29.7), underlining the insufficient vitamin D supply.…”
Section: Discussionsupporting
confidence: 65%
“…It can be expected that the number of PKU patients on a relaxed diet without AAM supplement will increase in the coming years because of the relatively new and successful cofactor therapy with tetrahydrobiopterin (BH 4 ) in patients with BH 4 -sensitive PKU. 9,10 These patients are at risk of continuous micronutrient deficiencies with all known long-term consequences. [11][12][13] In general, basic eating habits develop during early childhood and remain stable throughout life.…”
Section: Intake Of Micronutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,54 On the other hand, few other studies have shown that phenylketonuria patients following a strict diet supplemented with phenylalanine-free amino acid formulae were not at risk of developing deficiencies in these micronutients. 55,56 More studies are required to clarify these conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Phenylketonuria (PKU) is one of the most common congenital metabolic abnormalities caused by the mutation in the gene that codes for the phenylalanine hydroxylase enzyme (PAH; Gunduz et al, ). In the absence or disruption of the enzyme performance, impaired phenylalanine to tyrosine conversion, phenylalanine accumulation in the blood and tissues, and deficiency of tyrosine occurs (Thiele et al, ). The prevalence of PKU in Western and Northern European and Caucasian infants is about 1 in 10,000 (Fidika, Salewski, & Goldbeck, ).…”
Section: Introductionmentioning
confidence: 99%